Pengaruh Kualitas Pelayanan, Ketepatan Waktu Pengiriman dan Fasilitas Tracking Sistem Terhadap Kepuasan Pelanggan JNE Express Cabang Krakatau Medan - Yusuf, Immanuel; Alfifto, Alfifto (Universitas Medan Area, 2024)
Abstract This research aims to examine the influence of service quality, timeliness of delivery, and system tracking facilities on customer satisfaction. This research, it is hoped that we can find out how each of these variables influences customer satisfaction and the extent to which improvements in these variables can increase customer satisfaction. This research is descriptive research with a quantitative approach, which is measured using SPSS 26 program. Data collection is through distributing questionnaires. The population of this research was 100 customers of JNE Krakatau Branch in Medan City with samples using the purposive sampling method. Data analysis techniques are carried out using instrument tests, classical assumption tests, statistical tests, and hypothesis tests. Based on the research results, it shows that (1) service quality has a positive and significant influence on customer satisfaction at JNE Krakatau Medan Branch, (2) timeliness of delivery has a positive and significant influence on customer satisfaction at JNE Krakatau Medan Branch, (3) system tracking facilities do not affect customer satisfaction. has an effect and is not significant on customer satisfaction at JNE Krakatau Medan Branch.